2020
DOI: 10.1097/md.0000000000023162
|View full text |Cite
|
Sign up to set email alerts
|

Review of psychiatric comorbidities and their associations with opioid use in elective lumbar spine surgery

Abstract: The opioid epidemic is an ongoing concern in the United States and efforts to ameliorate this crisis are underway on multiple fronts. Opiate use is an important consideration for patients undergoing lumbar spine surgery with concurrent psychiatric diagnoses and more information is needed regarding the factors involved in these patients. That information may help guide opioid prescribing practices for individual patients with certain psychiatric conditions that are undergoing these procedures. This study was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…1). Characteristics of the included studies are reported in online Supporting Information Table S2 [20–79]. The included studies were published between 2003 and 2023 and had sample sizes ranging from 43 to 215,684 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Characteristics of the included studies are reported in online Supporting Information Table S2 [20–79]. The included studies were published between 2003 and 2023 and had sample sizes ranging from 43 to 215,684 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Opioid use was assessed in three studies. Depression was associated with greater opioid use at 1 year after surgery [54] but not with opioid use in‐hospital [34] or at 3 months following surgery [53].…”
Section: Resultsmentioning
confidence: 99%